La fusion de l’art littéraire et de la technologie numérique dans l’appréciation des contes traditionnels - Nardjas Zeghib (Multilinguales)
This article examines the role of digital literature in the learning process and explores how narratives are represented in the digital environment. The study focuses on the interaction between learners and the multimodal and animated elements present in digital narratives, as well as their ability to evoke affective and aesthetic responses. The data was collected during an activity where learners responded to textual conventions and literary features of a traditional story, both in its printed and digital versions. The analysis draws on literary and multimodal theories from narrative studies, reception aesthetics, multimodality, and linguistics to provide a comprehensive insight into the subject.